Transition in FSU and sub-Saharan countries: The role of institutions - Juhani Laurila (Bank of Finland, Institute for Economies in Transition (BOFIT), 2002)
This study compares transition processes in countries of Central and Eastern Europe, the former Soviet Union (FSU) and sub-Saharan Africa.By widening the scope from most- to least-developed transition economies, the study establishes the importance of a strong state with evolved institutional capacity to protect citizens, enforce property rights and generate social capital.The evidence presented further argues that enforceable, credible property rights with associated market discipline are among the best antidotes to corruption, shadow economies, criminal injustice and poverty.The presence of accountable institutions also influences economic growth and the ability of a country to attract trade and foreign direct investment.Consequently, when institutions of FSU and sub-Saharan countries develop to the point they become attractive to traders and investors from rich countries, their governments need to focus on abolition of barriers to trade, investment and capital.The author commends the recent reorientation of the international donor community towards encouraging recipient governments to commit credibly to increasing capacities of their state institutions with a view to supporting property-based rule of law and social order.
URN:NBN:fi:bof-201408072215
Keywords: 330; sub-Saharan Africa; former Soviet Union; property rights; institutions; growth; international trade; development assistance